The effectiveness of reels Instagram toward students’ English speaking Performance - Uswatun Khasanah; Chadafi, Muamar (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The purpose of this study was to find out how to use Instagram as a medium to teach students speaking skills and students' responses to Instagram treatment. This research is expected to be a reference for English teachers who have difficulty in teaching English and to encourage fluency for students and hope it will be useful for solving teacher problems. This research used a pre-experimental research design Because the researcher took one class as a sample so it will be in the form of an experimental one-group post-test. The data was gathered from 15 February 2024 til 18 February 2024 in the academic year 2023/2024. Based on the research results presented, it can be concluded that the use of Instagram Reels media is effective in improving students' speaking skills. This is supported by the increase in scores between the pre-test and post-test, which shows that the post-test scores are significantly higher than the pre-test scores. Data analysis using SPSS also shows that there is a significant difference between the pre-test and post-test scores. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted, which indicates that the use of Instagram Reels has a positive impact on students' speaking abilities. Overall, it can be concluded that the use of Instagram Reels media is an effective and recommended strategy for improving students' speaking skills, especially in school.